EFEK TEKNOLOGI, LINGKUNGAN DAN INDIVIDUAL YANG MEMPENGARUHI PENGGUNAAN E-COMMERCE TERHADAP KINERJA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) - Holilullah Holilullah; Muhammad Miqdad; Yosefa Sayekti (Jurnal Akuntansi dan Pajak, 2023)
The type of research used is explanatory research. The sample in this study were owners of SMEs in 31 sub-districts in Jember Regency registered with the Department of Cooperatives and Micro Enterprises in Jember Regency, totaling 134 owners. Data analysis tools are validity test, reliability test, classical assumption test and multiple linear regression analysis, hypothesis test and coefficient of determination test (R2) with the help of SPSS Statistics Version 22. The results of this study are (1) The results of multiple regression testing on Technological Factors on the Use of E-Commerce shows a positive and significant effect. This proves that the higher the Technological Factor, the higher the use of MSME E-Commerce in Jember Regency. (2) The results of multiple regression testing on Environmental Factors on the Use of E-Commerce shows a positive and significant effect. This proves that the higher the environmental factor, the higher the use of MSMEs in E-Commerce in Jember Regency. (3) The results of multiple regression testing on individual factors on the use of e-commerce shows a positive and significant effect. This proves that the higher the Individual Factor, the higher the use of MSME E-Commerce in Jember Regency. (4) The results of multiple regression testing on the use of e-commerce on the performance of SMEs in Jember Regency showed a positive and significant effect. This proves that the higher the use of E-Commerce, the higher the performance of SMEs in Jember Regency Keywords : Effects of Technology, Environment, E-Commerce and Micro, Small and Medium Enterprises (MSMEs)